Epidemiological study of prevalence of chlorpropamide alcohol flushing in insulin dependent diabetics, non-insulin dependent diabetics, and non-diabetics. Issue 6404 (19th November 1983) - Ng Tang Fui, S; Keen, H; Jarrett, R J; Strakosch, C; Murrells, T; Marsden, P; Stott, R
Abstract : An epidemiological study was carried out to compare the prevalence of facial flushing in non-diabetics, patients with insulin dependent diabetes, and patients with non-insulin dependent diabetes in response to 40 ml sherry taken 12 hours after 250 mg chlorpropamide or placebo, administered double blind in randomised order. A flush after chlorpropamide but not placebo was reported by 6.2% of non-diabetics (17/273), 9.7% of insulin-dependent diabetics (14/145), and 10.5% of non-insulin dependent diabetics (25/239), excluding those receiving long term chlorpropamide treatment. The differences were not significant. This response was unrelated to age, sex, body mass index, and family history of diabetes in all three groups. Patients taking long term chlorpropamide, however, showed a significantly (p less than 0.01) higher prevalence of flushing after both chlorpropamide and placebo (56.3%; 9/16) compared with the rest of the non-insulin dependent diabetics (16.7%; 40/239), the insulin dependent diabetics (6.9%; 10/145), and the non-diabetics (5.9%; 16/273). Patients receiving long term chlorpropamide would be expected to flush with sherry after a placebo tablet because of therapeutic plasma concentrations of the drug. It is concluded that there is no evidence of an increased prevalence of chlorpropamide alcohol flushing in response to the single challenge test in non-insulin dependent diabetics compared with insulin dependent diabetics and non-diabetics except in selected patients taking chlorpropamide long term. This study does not support the hypothesis that the chlorpropamide alcohol flush is a specific marker for a subtype of non-insulin dependent diabetes.